THE ROLE OF ISLAMIC EDUCATION IN CURBING DRUG ADDICTION AMONG THE YOUTH IN KATSINA STATE - Ibrahim, Abdulrahaman; Ayinla, Olawuwo Abdulfatai; Gidado Ph.D, Nuradeen Yanhoho (Journal of Higher Education and Academic Advancement, 2024)
One of the objectives of Islamic education is the total commitment to character building based on the ideals of Islamic ethics. It is the highest goal of Islamic education. Once a character is lost, it would be difficult to redevelop it. Education is not limited to training the mind only and pouring information into it, but it involves all aspects of human life such as religious, moral, intellectual and physical personality of the learner. Islam is a religion that emphasizes the purity of civilized human life. Purification is part of the faith that works to produce individuals who abide by Islamic law. The problem of drug abuse has been viewed seriously in recent years around the world. Therefore, prevention is very important to prove that Islam can solve various social problems. Drug addiction is a substance harmful to a person’s physical, spiritual (mental and emotional), and behavior when used. As a result of this effect, a person who uses drugs will become dependent on the drug and become addicted. In other words, drugs carry a very high risk that can be fatal. However, the dangers of drugs that are contagious in society today are given serious attention by Islam. This study discusses the causes of addiction among the young people in Katsina state and how to address the treatment of drug issues with a view to a religious perspective as an alternative that can enhance the spiritual heir to young. Thus, the Quran and Hadith of the Prophet SAW, as the primary references in Islam, have a vital role in resolving the problem of Muslims related to drugs.